Indirect autonomic nervous system activity assessment with heart rate variability in rats with cyclophosphamide-induced hemorrhagic cystitis treated with melatonin or agomelatine - Dobrek, Łukasz; Baranowska, Agnieszka; Thor, Piotr J. (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study : Melatonin (MLT) is reported to exert uroprotective effect due to its antioxidant/anti-inflammatory properties. It is unknown whether that effect also results from melatonin receptor activation, or it is attributed to the modulation of the autonomic nervous system (ANS) activity. Our purpose was to evaluate the effect of MLT and agomelatine (AMT) – melatonin receptor agonist on ANS activity, indirectly assessed by heart rate variability (HRV), in rats with cyclophosphamide-induced hemorrhagic cystitis (CP-HC). Material and methods : CP-HC was induced in all rats by four doses of cyclophosphamide given intraperitoneally (i.p.) at the dose of 75 mg/kg/dose. Rats were divided on three experimental groups and during induction of cystitis were treated i.p. with: (1) saline (control group); (2A/2B) MTL given at the dose of 40 or 100 mg/kg/dose; (3A/3B) AMT given at the dose of 40 or 100 mg/kg/dose. HRV recordings were performed in anesthetized rats at the eight day of the study. Results : Both 2A and 2B animals were characterized by an increase in all non-normalized components in HRV spectrum. Furthermore, normalized LF (nLF) increase along with normalized HF (nHF) decrease were demonstrated in 2B rats. AMT treatment resulted only in an increase in total power (TP) and very low frequency (VLF) in 3A animals. Conclusions : CP-HC rats treated with MLT were characterized by global ANS activity elevation, with a marked sympathetic tone predominance in subgroup 2B. Since the AMT treatment had no effect on autonomic function, it seems that melatonin modulates autonomic activity via non-receptor mechanisms.